Microencapsulation of natural antioxidant powder from Aloe vera (L.) skin using foam mat drying method - Narsih (2015)
Microencapsulation of natural antioxidant powder from Aloe vera (L.) skin using 10% maltodextrin, 0.3% tween 80 and drying at 600C produced free radical scavenging activity using DPPH (88.31%), total phenol (34.921%), and α tocopherol by HPLC (87.789mg/g). The results of GC-MS analysis as phyto-component were squalene (16.84%), 7 tetradecane (13.13%), limonene (14.17%), n-Hexadecanoic acid (11.91%) and α-Tocopherol (4.18%). And the results of FTIR analysis were phenol, aromatic, substituted alkenes, aromatic acid halide, aliphatic acid halide, eter R-O-R, Nitro NO2, Keton R-CO-R,vinilidene, carboxylic acid, metilene and OH. And the results of SEM analysis showed that drying product by foam mat method has a structure which is easier to absorb water and can dissolved in cold water. The result of this study indicated that microencapsulation on aloe vera skin powder improved the bioactive properties as contained phyto-component as antioxidant agent.